Integrating social sciences and islamic values in IHEIS (Islamic Higher Education Institutions): A multi-case study - Nuriman Nuriman; Yusnaini Yusnaini; Fauzi Fauzi (Jurnal Geuthèë: Penelitian Multidisiplin, 2026)
This study examines the integration of social sciences and Islamic values in Islamic Higher Education Institutions (IHEIs) as an effort to harmonize Islamic intellectual traditions with modern knowledge. The integration of sociology, anthropology, psychology, and political science is considered essential for developing graduates with analytical competence and strong moral foundations. This research employs a qualitative multi-case study approach investigates three IHEIs in Aceh, Indonesia. Data were collected through in-depth interviews, document analysis, and observations, and analyzed using thematic analysis. The findings reveal that integration is driven by two motivations: primary addressing complex social issues and strengthening academic competitiveness. However, the process faces challenges including epistemological tensions between traditions, methodological differences, and limited interdisciplinary faculty capacity. Despite these constraints, integration contributes to students’ critical thinking, moral awareness, and societal engagement. The study concludes that interdisciplinary integration can enhance the relevance of Islamic higher education while preserving its ethical and intellectual foundations.